Nondimensional analysis of single lap joint subjected to out-of-plane loading. (1st June 2015) - Tang, J.H.; Sridhar, I.; Srikanth, N.
Abstract: Transverse deflection of a single lap joint subjected to both in-plane and out-of-plane loadings is analyzed, incorporating nondimensional analysis. Solution from such analysis can then be exploited in obtaining the energy release rate and global mode mixity of a cracked single lap joint. Being contingent on debonding propensity of the crack tips, the kinetic energy absorption capacity in the event of low-velocity impact is examined based on global energy-balance consideration. Results reveal that calculations of change in impact energy level in experiment, as well as energy release rate and mode mixity in numerical models are comparable with nondimensional model. Though a gain in energy release rate is expected, the presence of in-plane loading also appears to improve the impact energy absorption capacity at high kinetic energy level. For a reasonably design estimate of low-velocity impact behavior of a single lap joint, the nondimensional analysis presented is considerably less cumbersome to handle.